Design and Implementation of a Climbing Robot Limb for Clinging to RoughWalls - Jodah, Mohammed; Rashid, Mofeed; Batbooti, Raed (Iraqi Journal for Electrical and Electronic Engineering, 2025)
In recent years, the urgent need for robotics applications in various sensitive work areas and high buildings has led to asignificant development in the design of robots intended for climbing rough surfaces. Where, attention became focusedon the ideal clinging mechanism. In this paper, a gripper of the climbing robot has been designed to achieve clingingon rough walls. The objective of this design is to be lightweight with high performance of clinging, therefore, a robotgripper has been designed based on a model of a limb inspired by the hand and claws of a cat, in which the robot clawswere implemented by fishing hooks. These hooks are arranged in an arc so that each hook can move independently onthe wall’s surface to increase the force of clinging to the rough wall. SolidWorks platform has been used to design theclinging limb and implemented using a 3D printer. In addition, the proposed design has been validated by performingseveral simulations using the SolidWorks platform. Experimental work has conducted to test the proposed design, andthe results proved the success of the design.